UTILIZATION OF AI TO ENHANCE STUDENT ENTREPRENEURSHIP ON SOCIAL MEDIA PLATFORMS - Sitorus, David Humala; Wasiman, Wasiman; Siagian, Mauli; Wage, Sunarto (Universitas Putera Batam, 2024)
This study examines the utilization of artificial intelligence (AI) in automating promotional content to enhance student entrepreneurship on social media platforms. By leveraging AI technologies, student entrepreneurs can efficiently generate, manage, and optimize promotional content, significantly improving engagement and reach. The study highlights key AI tools and algorithms that enable personalized and data-driven content creation, demonstrating their impact on marketing effectiveness. Conducted at Universitas Putera Batam with 100 student respondents, the research provides insights into the advantages and challenges of integrating AI into social media strategies for student-led businesses, ultimately fostering innovation and entrepreneurial growth in the academic environment